Os beija-flores e as pessoas: desvendando a contribuição da ciência cidadã e o efeito da urbanização nas interações com as flores - Bosenbecker, Camila Ferreira (2024)
Hummingbirds are known for their specialized nectar diet and play a vital role in maintaining ecosystems through pollination. However, these species are in decline globally due to habitat loss and climate change. Human-induced changes to their habitats not only threaten their interaction but also alter the composition of communities. On the other hand, some human activities, such as birdwatching, generate great interest, generating citizen science records that can contribute to a better understanding of hummingbird biology. This popular practice worldwide has enormous potential to provide valuable data on biodiversity. Therefore, this thesis investigates two aspects of the relationship between people and hummingbird-plant interactions: the potential of citizen science to contribute to scientific knowledge and the impact of urbanization on these interactions. The first chapter explores the role of citizen science in complementing the data collected by professional scientists using the Wikiaves platform. The results reveal that citizen-generated data can cover large geographical areas, capturing interactions not observed by scientists. Although there are limitations, such as the lack of data standardization and the focus on urban areas, these data are promising for biodiversity and conservation studies. It is important to emphasize that citizen science not only documents common species but also records of endangered species, offering a rich source of information for public policies as well as promoting general public involvement in science. The second chapter evaluates the changes in the structure of plant-hummingbird interaction networks along a gradient of urbanization. The results show that these interactions are largely generalized, with a high predominance of non-native plants, regardless of the level of urbanization. Although urban networks were generalized, the presence of native plants was associated with greater specialization in interactions, suggesting that native plant diversity plays a crucial role in promoting more complex networks and sustaining pollinators in urban landscapes. One convergence between the two chapters is that citizen science has great potential for monitoring and conserving biodiversity in urban areas. Engaging the public in data collection democratizes scientific knowledge and provides valuable data for researchers and environmental managers. In addition to generating robust data, citizen science strengthens the link between the population and nature, promoting awareness and engagement in environmental conservation. On the other hand, it is crucial that urban planners recognize the need to integrate biodiversity conservation into city planning. Only with appropriate public policies and community involvement will it be possible to reduce the negative impacts of urbanization and promote more sustainable and nature-friendly cities.